Spritualization Of New Media With Islamic Values Study Of Sa'id Nursi's Thinking In The Media Field - Adeni Adeni; H. M. Alfandi (STAI Bumi Silampari, 2023)
This article aims to study the contribution of Badi’uzzaman Said Nursi in the Islamic media field. His thoughts can be considered a solution to social problems caused by globalization. This study uses a qualitative method based on literature studies in which the primary data source is Risale-I Nur, the monumental work of Said Nursi. The results show that Said Nursi displayed